Comparison of Financial Distress Measurement Models in Technology Companies on the Indonesia Stock Exchange in 2022-2024 - Kezia Sugiwan; Fredella Colline (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The objectives of this study are: (1) to measure the potential financial distress of technology companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period using the Altman Z-Score, Zmijewski X-Score, and Grover G-Score methods; (2) to examine differences in the results among these methods; and (3) to determine the method with the highest level of accuracy. This study employs a quantitative approach using secondary data in the form of annual financial statements. The research sample consists of 29 companies with a total of 87 observations. The results of the analysis using the Altman Z-Score, Zmijewski X-Score, and Grover G-Score indicate that each method identifies three companies as potentially experiencing financial distress, with different company compositions across methods. The Kruskal–Wallis test results also show a statistically significant difference among the methods in predicting financial distress. Based on the accuracy test results, the Grover G-Score method is the most accurate method in this study. This research provides practical implications as an early warning tool for management and investors in assessing the risk of financial distress in technology companies.